The Study on Mechanical and Electrical Properties of AA6061/Snail Shell Composites - N.E. Udoye; G.E. Ezike; O.S.I. Fayomi; J.O. Dirisu (International Journal of Chemical Engineering)
Metal matrix composites are in high demand for various applications in the industrial sector and engineering firms. Therefore, new materials with enhanced mechanical and ecologically favourable characteristics must be designed and produced. This study focuses on the possibility of developing an aluminium matrix composite using agro-waste materials as reinforcement in preference to other industrial chemicals and materials. The morphological analysis carried out on the AA6061 + 15% snail shell at 100 μm showed the formation of homogenous particle size with stepped crystals. The micrographs of the developed composite were obtained using XRD (X-ray diffraction analysis), which indicated the presence of calcium and hydroxyapatite from the snail shell on the aluminium composite. Electrical analysis performed on the developed composite showed an increase in the conductivity from 32.03 Ωm−1 to 34.59 Ωm−1 as the snail shell reinforcements were increased, thus improving the capability of the developed MMC to transfer electricity due to the occurrence of the snail shell particulate within the composite.